From Classroom to Clinic: Digital Transformation in Health Professional Education and Training Delivery - Choice Orise (INTERNATIONAL JOURNAL OF HEALTH AND PHARMACEUTICAL RESEARCH, 2026)
Health professional education is being reshaped by digital tools at the same moment the clinical systems graduates enter are themselves undergoing rapid digital change, yet the literature linking these two transformations remains fragmented across separate research communities. This integrative review synthesises a body of scholarship spanning educational technology, professional development, and digital health delivery to trace how change in the learning environment connects to change in the practice environment. The review draws together work on artificial intelligence and personalised learning, technology integration in instruction, professional development for educators, and the parallel emergence of telehealth, health informatics, and digital operations in care settings. Three connected patterns recur across this work: digital tools alter how knowledge and skills are delivered rather than simply digitising existing content; the benefits reported are conditional on infrastructure, teacher and clinician capability, and governance rather than guaranteed by technology alone; and a persistent gap separates the digital fluency cultivated in formal education from the digital systems professionals must operate in practice. The evidence is largely conceptual and descriptive rather than experimental, so claims about effectiveness are reported with corresponding caution. These patterns suggest that preparing health professionals for digitally mediated practice is less a matter of adding technology to curricula than of aligning educational design, workforce development, and health-system digital governance. The review offers a bridging framework for that alignment and identifies where the absence of comparative and longitudinal evidence most constrains current understanding, with implications for educators, health-system leaders, and policymakers working across the classroom-to-clinic continuum.